Further Analysis of Copper Chelate Solution with Murexide - Gao, Hong-Wen; Zhang, Yu-Rong (Asian Journal of Chemistry, 2010)
The chelated reaction of copper(II) with murexide at pH 12 is furtherstudied for analysis of characteristic factors of the chelate formed. Besides,the determination of trace amounts of copper in metal material and wastewater is made in this part using β-correction principle. For this updatedtheory, to completely eliminate the effect of excess ligand in its Cu(II)chelated solution, the sensitivity, accuracy and precision are all improvedfor micro determination, but also it brings out the satisfactory result foranalysis of the chelate characteristic factors including complexation ratioand practical molar absorptivity using spectrophotometric method. Theresults show that the chelate formed is expressed by Cu (murexide)2 andBeer's law obeyed over the concentration range 0-4.00 mg/L copper withthe detection limit of copper 0.05 mg/L. The recovery is between 97.4 and104% with the relative standard deviation less than 4.4%.